2020
DOI: 10.3390/f11101038
|View full text |Cite
|
Sign up to set email alerts
|

Policies Drive Sub-National Forest Transitions in Vietnam

Abstract: Vietnam has seemingly been able to shortcut the forest transition (FT) by quickly moving to the reforestation phase. Provincial-level forest cover and socio-economic trends are, however, not necessarily compatible with a standard FT framework. This article compares forest cover change and associated policy reforms in two provinces. Bac Kan is one of the poorest provinces in Vietnam, and has, after years of deforestation and forest degradation, expanded its forest cover during the past two decades. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
9
0
2
Order By: Relevance
“…The results identified that the government had issued several policies to help the investors and farmers involved in this project. However, concerns about their practice were raised, some of which included: the low percentage of dividend sharing for farmers, unclear land use rights, and the inadequate application of policies to reality (Traedal & Angelsen, 2020). Moreover, in the study area, rubber plantations expanded into to cropland areas.…”
Section: Resultsmentioning
confidence: 99%
“…The results identified that the government had issued several policies to help the investors and farmers involved in this project. However, concerns about their practice were raised, some of which included: the low percentage of dividend sharing for farmers, unclear land use rights, and the inadequate application of policies to reality (Traedal & Angelsen, 2020). Moreover, in the study area, rubber plantations expanded into to cropland areas.…”
Section: Resultsmentioning
confidence: 99%
“…Four articles empirically linked forest gain to policy changes. In Bac Kan, Vietnam, new land entitlements led to forest regrowth on land previously under shifting agriculture [ 33 ]. In China, policies encouraging farmers to maximize labor productivity in land use resulted in more select land use, and consequently in reclamation and resurgence of ecological services elsewhere [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 'pathway hypothesis' was put forward and fully developed and widely recognized, including 'economic development pathway' and 'forest scarcity pathway,' 'globalization pathway,' 'national policy pathway' and 'agroforestry intensive pathway' (Ellis et al, 2021; Lambin & Meyfroidt, 2010; Rudel et al, 2005; Schelhas et al, 2021). Recent studies indicate that food imports (Belay et al, 2015); topography and proximity to plantations (da Silva et al, 2016), economic globalization (Li et al, 2017; Liu et al, 2017); conservation and restoration efforts (Chazdon, 2019); economic, policy interventions, and governance (Chazdon et al, 2020; Cochard et al, 2020; Liu et al, 2017; Saraiva et al, 2020; Tradal & Angelsen, 2020) influence the magnitude and timing of forest transition. Recent analyses have investigated the combined effects of multiple forest transition pathways (Jadin et al, 2016; Singh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%